Synthesis of Chimeric Thiazolo‐Nootkatone Derivatives as Potent Antimicrobial Agents. (9th June 2021) - Alkhaibari, Ibrahim S.; Raj K. C., Hansa; Alnufaie, Rawan; Gilmore, David; Alam, Mohammad A.
Abstract: Nootkatone, an approved insecticide, is a well‐known natural product from grapefruit. A series of fused‐thiazole derivatives of nootkatone have been synthesized, and these new compounds were tested against several strains of bacteria. Some of these compounds are found to be potent antimicrobial agents against Staphylococcus aureus and Enterococcus faecium with minimum inhibitory concentration (MIC) values as low as 1.56 μg/mL. The lead compound is bactericidal and very potent against S. aureus persisters. These compounds are nontoxic to human cancer cell lines at 10 μm concentration. Abstract : Persistence against persisters : Methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant enterococci (VRE) are widespread drug‐resistant bacteria. A series of novel chimeric thiazolo‐nootkatone derivatives are reported. These natural‐product‐derived chimeric compounds are potent growth inhibitors of planktonic MRSA and VRE with MIC values as low as 1.56 μg/mL. Some of these compounds are potent against persisters and bacterial biofilms.